Manganese nodules in Jurassic limestone of the Southern Alps in Slovenia - Ogorelec, Bojan; Buser, Stanko; Mišič, Miha (Geologija, 2006)
One of geological peculiarities in the Julian Alps is red pelagic limestone containing manganese nodules. They are encountered at several localities in the Bovec, Trenta and Km area, occurring in some metres thick horizon of the Upper Liassic age. The nodule forms are disc-like attaining up to 12 cm in diameter. Mineral composition is characterized by pyrolusite, psilomelane, manganite and hausmannite. The shear of Mn in the nodules is low ranging from 0,8 % to 3,5 %. The Fe amount attains up to 1,7 %, in some samples, however, Fe exceeds Mn. At Mangart and at Begunjščica, Mn ore beds occur in a thinner horizon in a sequence of slate, radiolarite and crinoidal limestone. Herein, the amount of MnO reaches up to 60 %.